2021
DOI: 10.2166/nh.2021.007
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic interval estimation of design floods under non-stationary conditions by an integrated approach

Abstract: Quantifying the uncertainty of non-stationary flood frequency analysis is very crucial and beneficial for planning and design of water engineering projects, which is fundamentally challenging especially in the presence of high climate variability and reservoir regulation. This study proposed an integrated approach that combined the Generalized Additive Model for Location, Scale and Shape parameters (GAMLSS) method, the Copula function and the Bayesian Uncertainty Processor (BUP) technique to make reliable prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Moreover, existing design standards of flood protection engineering are mostly based on stationary assumptions when calculating return levels of the design storm (Hossain et al, 2021). However, studies have reported that extreme precipitation and runoff series show non‐stationary characteristics such as significant trends and change points, which means they no longer follow the stationary assumption (Liu et al, 2022a; Milly et al, 2008; Tramblay et al, 2012; Zhou et al, 2022). If return levels of precipitation extremes in engineering design are still calculated based on stationary assumptions under non‐stationary conditions, two situations will occur: (1) underestimation of design storms, which will result in underestimation of failure risks for hydrological projects; (2) overestimation of design storms, which will result in wasted economic costs due to the overestimation of failure risks for hydrological projects (Rodrigues et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, existing design standards of flood protection engineering are mostly based on stationary assumptions when calculating return levels of the design storm (Hossain et al, 2021). However, studies have reported that extreme precipitation and runoff series show non‐stationary characteristics such as significant trends and change points, which means they no longer follow the stationary assumption (Liu et al, 2022a; Milly et al, 2008; Tramblay et al, 2012; Zhou et al, 2022). If return levels of precipitation extremes in engineering design are still calculated based on stationary assumptions under non‐stationary conditions, two situations will occur: (1) underestimation of design storms, which will result in underestimation of failure risks for hydrological projects; (2) overestimation of design storms, which will result in wasted economic costs due to the overestimation of failure risks for hydrological projects (Rodrigues et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Design flood value associated with a specific return period (e.g., 100-year that is most commonly used in relevant studies) is traditionally estimated based on flood frequency analysis through statistical approaches [6]. Recently, with the concept that stationarity is dead [4], various methodologies using a probabilistic model of flood frequency considering nonstationarity have been introduced [7][8][9][10][11][12][13][14][15]. Khaliq et al [16] provide a comprehensive review of these approaches, including the incorporation of trends in distribution parameters, trends in statistical moments, etc.…”
Section: Introductionmentioning
confidence: 99%